"Captains Courageous": A Story of the Grand Banks - Kipling, Rudyard, 1865-1936; Taber, I. W. (Isaac Walton), 1857-1933 (Salt Lake City, UT : Project Gutenberg, 2000)
"Captains Courageous: A Story of the Grand Banks" by Rudyard Kipling is a novel published in 1897. When fifteen-year-old Harvey Cheyne Jr., the pampered son of a railroad tycoon, falls overboard from a steamship, he's rescued by a fishing schooner off the Grand Banks. Unable to convince the crew of his wealth or persuade them to take him home, Harvey must work alongside the fishermen for an entire season at sea, learning hard lessons about labor, humility, and manhood in the unforgiving world of the cod fishery. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Captains_Courageous
Release date is 2000-06-01
Produced by Bill Stoddard and David Widger
Keywords: Sea stories; Bildungsromans; Children of the rich -- Fiction; Saltwater fishing -- Fiction; Fishing boats -- Fiction; Teenage boys -- Fiction; Rescues -- Fiction; Fishers -- Fiction; Grand Banks of Newfoundland -- Fiction